Primary Hypoparathyroidism - Misdiagnosed as Epilepsy (Journal of Medicine, 2018)
Absent or inappropriately low intact parathyroid hormone along with hypocalcemia is the diagnostic criterion of hypoparathyroidism. Clinically, hypoparathyroidism manifests predominantly as neuromuscular dysfunction caused by hypocalcemia. We present here a case of hypoparathyroidism wrongly and ineffectively treated as epilepsy for six years prior to reporting to our hospital. Hypoparathyroidism was diagnosed in our patient on the basis of low serum calcium (ionized and total), high phosphate and very low IPTH levels in face of normal magnesium levels along with radiological evidence of cerebral calcification.J MEDICINE JUL 2018; 19 (2) : 133-135